Georgia Women : Their Lives and Times - Clark, Kathleen Ann; Chirhart, Ann Short (Book collections on Project MUSE., 2014)
Women were leading actors in twentieth-century developments in Georgia, yet most histories minimize their contributions. The essays in the second volume of Georgia Women, edited by Ann Short Chirhart and Kathleen Ann Clark, vividly portray a wide array of Georgia women who played an important role in the state's history, from little-known Progressive Era activists to famous present-day figures such as Pulitzer Prize--winning author Alice Walker and former First Lady Rosalynn Carter. Georgia women were instrumental to state and national politics even before they achieved suffrage, and as essays on Lillian Smith, Frances Pauley, Coretta Scott King, and others demonstrate, they played a key role in twentieth-century struggles over civil rights, gender equality, and the proper size and reach of government. Georgia women's contributions have been wide ranging in the arena of arts and culture and include the works of renowned blues singer Gertrude "Ma" Rainey and such nationally prominent literary figures as Margaret Mitchell, Carson McCullers, and Flannery O'Connor, as well as Walker. While many of the volume's essays take a fresh look at relatively well-known figures, readers will also have the opportunity to discover women who were vital to Georgia's history yet remain relatively obscure today, such as Atlanta educator and activist Lugenia Burns Hope, World War II aviator Hazel Raines, entrepreneur and carpet manufacturer Catherine Evans Whitener, and rural activist and author Vara A. Majette. Collectively, the life stories portrayed in this volume deepen our understanding of the multifaceted history of not only Georgia women but also the state itself. Published with the generous support of the Honorable Dr. M. Louise McBee